Materials for the Bibliography of Klymentiy Hankevich - Pylypovych, Volodymyr (Sententiae, 2025)
The author provides the most complete bibliography of Klymentiy Hankevich’s book and press publications from 1868–1909, printed in Ukrainian, German, Polish and French.